Inverse association for diagnosis of Alzheimer's disease subsequent to both melanoma and non‐melanoma skin cancers in a large, urban, single‐centre, Midwestern US patient population. (17th April 2018) - Ibler, E.; Tran, G.; Orrell, K.A.; Serrano, L.; Majewski, S.; Sable, K.A.; Thiede, R.; Laumann, A.E.; West, D.P.; Nardone, B.
Abstract: Background: Although literature demonstrates a decreased risk of Alzheimer's disease (AD) in individuals with various cancers, including squamous cell cancers (SCC) and basal cell cancers (BCC) comprising non‐melanoma skin cancers (NMSC), there is a paucity of literature to substantiate an association between malignant melanoma (MM) and AD. Objective: The aim of this study was to determine whether an association exists between MM and AD as well as for NMSC and AD. Methods: A large urban, Midwestern, US, single‐centre, medical record (EMR) data repository was searched between January 2001 and December 2015, to identify all patients at age ≥60 and <89 years with a clinic follow‐up of at least 1 year and no diagnosis for AD, MM or NMSC at the time of the study entry. Data collected included age, gender, race and duration of follow‐up. MM and NMSC were detected by ICD‐9 codes and ICD‐10 codes. Incident diagnosis of AD was also detected by ICD‐9 and ICD‐10 codes. Logistic regression analysis was utilized to obtain crude and adjusted odds ratios (ORs). Results: Data for a total of 82 925 patients with known race and gender and were detected. After adjusting for confounding factors (race, gender, age, cerebrovascular disease, peripheral vascular disease and diabetes), there was a significant decreased risk of subsequent AD in patients with MM (OR: 0.39; 95% CI: 0.16–0.96; P = 0.042) as well as in patients with BCC (OR: 0.18; 95% CI: 0.08–0.45; P < 0.0001) and for patients with SCC (OR: 0.08; 95% CI: 0.01–0.56; P = 0.013). Conclusion: These findings add to the growing body of evidence for a decreased risk of AD in patients with various cancers and highlight the need for ongoing research to elucidate both neurologic and biologic mechanisms that may underlie this apparent inverse association.